BENTUK LEMBAGA PENYIDIKAN YANG MANDIRI DAN PROFESIONAL DI INDONESIA - Amin Razki Baadi (Fakultas Hukum Universitas Dayanu Ikhsanuddin, 2022)
ABSTRACT This study aims to determine two things namely. First, to find out the model of an independent and professional investigative institution. Second, to find out the relevance of the investigation function carried out by the National Police Criminal Investigation Agency. The approach method in this research is normative juridical. By using data collection techniques by means of library research. The results of the study show that the investigative authority requires the unification of investigative institutions which are formed in a separate container as a model of independent and professional institutions, so that there is no pluralism in the investigative authority, and the establishment or formation of investigative institutions in one institution, then the existence of the Criminal Investigation Agency which is still a part of the Polri institution becomes irrelevant, it must be separated from the elements of the Polri organization into a separate institution.